2007
DOI: 10.1007/s11461-007-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil properties in forest gaps and under canopy in broad-leaved Pinus koraiensis forests in Changbai Mountainous Region, China

Abstract: The species composition and diversities, and soil properties under canopy gaps in broad-leaved Pinus koraiensis forests were studied in the Changbai Mountains. The results indicated that the species composition and diversities in gap were different from those under canopy. The Shannon-Wiener index, evenness index, and abundance index in gap were higher than those under canopy in the seedling layer, while the community dominance in the seedling layer increased in closed canopy. The physicochemical properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Approximately 20 mg powder was weighed and put into 25 mL deionized water to determine TN and TP concentrations with the same method as used for the water samples [ 43 ]. The powder was also used to determine TOC content using the potassium dichromate method according to the national standard method in China (GB 7857–87) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 20 mg powder was weighed and put into 25 mL deionized water to determine TN and TP concentrations with the same method as used for the water samples [ 43 ]. The powder was also used to determine TOC content using the potassium dichromate method according to the national standard method in China (GB 7857–87) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The openness of the canopy induced a significant decrease of soil pH at the edge of the gap, independently from its size, but no difference occurred in comparison to the closed canopy. Zhang & Zhao (2007) found no significant difference for soil pH between canopy gaps and closed-canopy sites in broad-leaved Pinus koraiensis forests. Kooch et al (2010) reported a higher amount of pH for the large gaps in comparison to the medium gaps.…”
Section: Soil Responses To Forest Canopy Gapsmentioning
confidence: 59%
“…Moreover, some of the soil chemical characteristics such as SOC and total N showed a significant decrease in the center of gaps, independently from their size. Studies on the correlation between canopy gap size and BD have provided inconsistent results; correlation was found positive in broad-leaved Pinus koraiensis forests (Zhang & Zhao 2007) or absent in old-growth Tsuga canadiensis forests (Schliemann & Bockheim 2014). The lack of correlation of BD with the textural component of the soil made this result hard to fathom, but soil compaction due to the seedling recruitment (Muscolo et al 2010) cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were a large number of larger, mature trees among the living trees that have developed root systems and are therefore not significantly affected by the reduced groundwater level. By creating environmental heterogeneity in terms of light availability, gap disturbances play a key role in forest regeneration as well as in the establishment and development of tree species with different ecological recruitment patterns (Runkle 1989;Peterken 1996;Mountford 2006;Zhang et al 2006;Li et al 2013). Gapbased restoration provides a flexible system that Fig.…”
Section: Discussionmentioning
confidence: 99%